Peptídeos cíclicos em espécies do semiárido brasileiro e uma cultivada: caracterização e atividade biológica - Pinto, Meri Emili Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Brazil has one of the largest biodiversity in the world, however only a few plant-derived peptides have been studied from our biomes, constituting a rich source of peptides with interesting structural features and ecological functions, and so far, with potential pharmacological properties. In this study are described the investigation of orbitides and cyclotides in 24 species from plants. The orbitides refer to all N-to-C cyclized peptides from plants that do not contain disulfides and cyclotides, mini-proteins group characterized by a cyclic topology, collectively known as cyclic cystine motif (CCK) conferring them with remarkable stability. After the specific analysis for these compounds, was possible to select three species for to isolated your peptides: J. ribifolina, H. calceolaria e B. vulgaris. J. ribifolia (Pohl) Baill (syn. Adenoropium ribifolium Pohl, J. gossypifolia var. ribifolia (Pohl) Müll.), known as “pinhão-manso” and “pinhão rasteiro”, is a shrub of the Euphorbiaceae family that commonly grows in the semiarid region of northeastern Brazil. Plants of the genus Jatropha, which comprises approximately 175 species, have been established as a rich source of bioactive compounds such as alkaloids, terpens, lignans, flavonoids and cyclic peptides, so called orbitides. From the EtOH extracts of the J. ribifolia, collected in the states of Paraíba, an octapeptide cyclic, was isolated by a multi-step chromatography procedures, including HPLC. Conformational analysis of these peptides has been evaluated by using of NMR experiments and simulated annealing molecular dynamics. The synthesis of the new cyclic peptides were accomplished by solid-phase peptide synthesis (SPPS)-Fmoc/tBu. The antimicrobial, citotoxity and antimalarial activities are being evaluated for both the circular and linear synthetic form of the novel orbitide from J. ribifolia. Ribifolin (IC50 41.92 μM) was moderately effective against the Plasmodium...

O Brasil tem uma das maiores biodiversidades do mundo, no entanto poucos peptídeos derivados de plantas tem sido estudados desse bioma, constituindo uma rica fonte para buscar peptídeos com características estruturais e funções ecológicas interessantes. Neste estudo são descritos a investigação de orbitídeos e ciclotídeos em 24 espécies vegetais. Os orbitídeos referem-se a todos os peptídeos cíclicos ciclizados N-C que não apresentam ligação dissulfeto. Os ciclotídeos, grupo de mini- proteínas caracterizam-se por apresentar uma estrutura (CCK ) conferindo –lhes uma notável estabilidade. Após a análise específica para estes compostos, foi possível selecionar três espécies para prosseguir com os estudos de isolamento: J. ribifolina , H. calceolaria e B. vulgaris . J. ribifolia ( Pohl ) Baill ( syn. Adenoropium ribifolium Pohl, J. gossypifolia var. ribifolia ( Pohl ) Müll. ), conhecida como pinhão -manso e pinhão rasteiro, é um arbusto da família Euphorbiaceae, que geralmente cresce na região semi-árida do nordeste brasileiro. Plantas do gênero Jatropha, compreendem cerca de 175 espécies, ricas em compostos bioativos, como alcalóides, terpenos, lignanas, flavonóides e orbitídeos. A partir dos extratos etanólico de J. ribifolia, coletada no Estado da Paraíba, um novo octapeptídeo cíclico foi isolado por métodos cromatográficos, incluindo HPLC. A análise conformacional foi estabelecida por dados de RMN e dinâmica molecular. A síntese desse orbitídeo foi realizada por síntese em fase sólida (SPPS)-Fmoc/tBu. As atividades antimicrobiana, citotóxica e antimalárica foram avaliadas, para ambas as formas: circular e seu análogo linear sintéticos. Ribifolina (IC50 41,92 mM) foi moderadamente eficaz contra a o Plasmodium falciparum 3D7, mas seu análogo linear (IC50 519μmol / L) mostrou-se fraco em inibir a sobrevivência do parasita. Estes compostos não apresentam qualquer citotoxicidade contra...
Keywords: Quimica organica; Peptídeos; Dinamica molecular; Peptides